Research on the Pathway for Improving the Practical Teaching Quality of Health Management Specialization under the Integration of Courses, Practical Training and Certifications - Xing, Jianhong (Education Insights, 2025)
The "Healthy China 2030" planning outline has driven the rapid development of the health management industry. Consequently, the market demand for comprehensive health management technical and skilled professionals equipped with practical abilities, professional qualifications, and competitive literacy has been continuously increasing. The integration of jobs, courses, competitions, and certificates serves as the core model of comprehensive education within the vocational education framework. This model effectively connects four fundamental educational elements: professional positions, academic courses, skill competitions, and industry certificates. It acts as a crucial mechanism to resolve prevalent issues, such as the mismatch between supply and demand in practical teaching for the health management major, the devaluation of practical training, and singular evaluation methods. This article adopts a comprehensive methodology combining literature research, industry investigation, and teaching practice review to systematically identify existing challenges in current practical teaching frameworks. Furthermore, it elucidates the internal logic of integrating jobs, courses, competitions, and certificates, alongside the deep coupling of practical teaching methodologies. By incorporating the design of ideological and political education into the curriculum, this study proposes systematic quality improvement pathways across five key dimensions: modularized practical course reconstruction, integrated training and competition platform construction, 1+X certificate integration teaching implementation, dual-qualified practical teacher cultivation, and the establishment of a multi-dimensional teaching evaluation system. Ultimately, this research provides supporting guarantee mechanisms to offer a feasible reference for the enhancement of practical teaching in health management majors at vocational colleges.